1971
DOI: 10.1192/bjp.118.547.689
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study into Puerperal Depression

Abstract: SummaryA prospective study of mood changes through pregnancy and puerperium was undertaken by a research group centred on the North Middlesex Hospital, Edmonton, London. Data collected from 189 women revealed an evolution of mood changes in those who later developed puerperal depression, which was characterized by anxiety at the first ante-natal visit, elation during later pregnancy and depression in the puerperium. The findings were in agreement with other workers in this field. The arguments in favour of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
3
2

Year Published

1977
1977
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(80 citation statements)
references
References 7 publications
3
72
3
2
Order By: Relevance
“…Widely ranging rates of depression during pregnancy have been found: for example from 27% to 62% [3][4][5]. A comparison between Pakistani and Canadian women showed a higher proportion of Pakistani women (48.4%) with antenatal depression than aboriginal (31.2%) and Caucasian (8.6%) Canadian women [6].…”
Section: Introductionmentioning
confidence: 99%
“…Widely ranging rates of depression during pregnancy have been found: for example from 27% to 62% [3][4][5]. A comparison between Pakistani and Canadian women showed a higher proportion of Pakistani women (48.4%) with antenatal depression than aboriginal (31.2%) and Caucasian (8.6%) Canadian women [6].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found the presence of postpartum blues to be positively associated with a history of premenstrual tension, 6 acrytngbaby, a vomiting baby, or a baby who gives the mother bad nights. 7 The research of Paykel and assoctates 8 suggests that the blues may indicate a tendency toward postpartum depression. In their study, moderate to severe postpartum blues had been previously noted in six (85%) of the seven women with postpartum depression as opposed to 16 (31 %) of the 52 women without postpartum depression.…”
Section: Postpartum Mental and Physical Problemsmentioning
confidence: 98%
“…Elation during late pregnancy is acommon occurrence. Dalton (1971) found that it was present in 64~o of women with puerperal depression, compared with only 26 ~o of normal women. Patients who experienced the sequence of euphoria in pregnancy followed by post-partum depression described their pregnant state in such terms as "blissful", "never so well in my life", "walked miles with ease" and "boundless energy".…”
Section: Relation Of Prolactin To Ovarian Hormones and Dysphoriamentioning
confidence: 99%
“…For example, Dalton (1971), who emphasizes the progesterone deficiency idea, and who claims good results in many cases with progesterone treatment, appears to be describing mostly a syndrome of premenstrual irritability and hostility, rather than depression as such. Similarly, Backstrom & Carstensen (1974) presented impressive evidence for low progesterone levels in women with "premenstrual anxiety."…”
Section: Relation Of Prolactin To Ovarian Hormones and Dysphoriamentioning
confidence: 99%